Mobile Service Technician 4.0 – Knowledge-Sharing Solutions for Industrial Field Maintenance - Kaasinen, Eija; Aromaa, Susanna; Väätänen, Antti; Mäkelä, Ville; Hakulinen, Jaakko; Keskinen, Tuuli; Elo, Joona; Siltanen, Sanni; Rauhala, Ville; Aaltonen, Iina; Hella, Juho; Honkamaa, Petri; et al. (Interaction design & architecture(s), 2018)
With the fourth industrial revolution, Industry 4.0, many work tasks are becoming knowledge intensive. At the forefront of the change are workers that are already mobile, working in the field with customers. We describe the human-centred design process that resulted in the Mobile Service Technician 4.0 concept. The concept illustrates how industrial field maintenance work could benefit from knowledge-sharing solutions based on Industry 4.0. The solutions utilize industrial internet, virtual and augmented reality as well as wearable technologies to improve mobile service technicians’ daily work performance and work satisfaction. The Mobile Service Technician 4.0 concept illustrates the user experience of future maintenance work: feeling competent, feeling connected to the work community, and feeling of success and achievement by being better prepared for maintenance visits, getting situationally relevant support in maintenance operations, sharing knowledge with peers, and making maintenance reports effortless.